Probing CPT breaking induced by quantum decoherence at DUNE - Carrasco Martínez, Juan Carlos (2019)
We consider a beyond standard physics scenario, where neutrino is considered as an open quantum system. In order to have that consideration we use the Lindblad master equation, which introduce the quantum phenomena called decoherence. In that context we explore one of the most exotic of its consecuences, the CPT violation. We work in three avor generation case where making the SU(3) decomposition of the operators we encounter that there exist fteen parameters in the decoherence matrix that explicitly violate CPT. Regarding four of those parameteres we choose one case of decoherence which will be tested at DUNE.